Prevalence of pelvic organ prolapse in women, associated factors and impact on quality of life in rural Pakistan: population-based study - Abdul Hakeem Jokhio; Raheela Mohsin Rizvi; Christine MacArthur (BMC, 2020)
Abstract Background Pelvic organ prolapse (POP) is a gynecological condition resulting from pelvic floor dysfunction in women. The objective of this study is to estimate "the prevalence of pelvic organ prolapse" associated factors, duration and impact on women's quality of life in rural Pakistan. Methods A cross-sectional study was conducted with a three stage random sampling strategy. Three health centers were selected and selected Lady Health Workers from each health center interviewed a random sample of women in their households. The interview used a structured questionnaire to collect symptom data. Female gynaecologists then conducted a clinical examination at the local health center on women who reported symptoms of prolapse to verify and grade pelvic organ prolapse using Baden-Walker classification system. Results Among the 5064 women interviewed (95.8% response rate), 521 women had clinically confirmed POP, a prevalence of 10.3% (95% CI 9-11%). Among women with POP 37.8% had grade III or IV prolapse. Women with four or more children had the highest proportion of pelvic organ prolapse (75%) followed by women aged 36-40 years (25%).Among women with POP, 60.8% reported their quality of life as greatly or moderately affected; 44.3% had it for more than 5 years; and 78.7% never consulted a doctor. Conclusions Pelvic organ prolapse is highly prevalent in rural Pakistan, impacts on women's everyday lives and remains mainly untreated. Measures should be taken to provide health care services to reduce this burden of disease among women.